ANALYSIS OF THE EFFECT OF THE ADDITION OF LATITUDE STONE AS A CEMENT SUBSTITUTION ON THE COMPRESSIVE STRENGTH OF MORTAR - Gani, Moh Hari Febriana; Aidulghani, Bachtiar; Pangestu, Agung; Roesdiana, Tira (Politeknik Siber Cerdika Internasional, 2025)
In this study, the effect of adding latitude stone as a substitute for cement on the compressive strength of mortar in the manufacture of construction materials was analyzed to produce building materials with better quality. One of the ingredients in the manufacture of mortar is cement with the main formers is calcium. The addition of laterstone is an effort to increase the calcium element needed in the pozzolanic reaction when mixed with SIO2 in laterstone. The purpose of this study was to increase the compressive strength of mortar by adding laterstone as a substitute for cement. The research method used is a quantitative experimental method with data collection from laboratory research and using laterstone powder that passes the 200 sieve, in mortar mixes with percentage variations of 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% and 10%. The proportion of mortar mixture in this study used a ratio of 1: 3 (Cement: Sand) with a cement water factor (FAS) of 0.5 and was carried out using a compressive strength tool on a 5cm x 5cm x 5cm cube-shaped mortar at a time (age) of 7, 14, 21 and 28 days. Various tests were conducted on the materials and specimens to analyze the compressive strength and mass density of the mortar. The results of this study showed that the mortar achieved the highest compressive strength of 20.33 MPa with 3% laterstone mix variation at the age of 28 days. Mortar with more than 3% laterstone mixture variation will result in a decrease in compressive strength, thus reducing the compressive strength. This can be one solution to reduce the use of cement while reducing the exploitation of limestone mountains in Indonesia.